Existence Of Cultural Glocalization Supporting Elements In the Culture of Indonesian Culture - Rudi Umar Susanto; Syamsul Ghufron (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
AbstractIn the development of culture always requires an object to show progress. Various aspects include one of the elements of cultural glocalization. Technology has facilitated people in various parts of the world to exchange information about their respective cultures at every second of human life. Modern, such as music, clothing, singing, educational patterns and patterns of social life. However, it turns out that not all parties can share information equally. Developed countries are more dominant in conveying information about their culture and interests to developing countries. In this study, it shows the percentage of elements supporting cultural glocalization, namely aspects of traditional games and aspects of traditional sports. Keywords: Glocalization, Culture, Existence, Games and Traditional Sports